Peran TPQ dalam Meningkatkan Kualitas Kemampuan Baca Al-Qur’an pada Anak: Studi Kasus di TPQ Darul Fallah 2 Japanan Mojowarno Jombang - Eny Fatimatuszuhro Pahlawati; Eko Hadi Wardoyo; Putri Maulida (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2025)
This study aims to determine the role of TPQ in improving the quality of children's Qur'an reading ability at TPQ Darul Fallah 2 Japanan Mojowarno Jombang. This study uses a qualitative descriptive approach. Data collection uses observation, interview and documentation techniques with deductive and inductive analysis techniques. The results of the study indicate that the role of the Al-Qur'an Education Park (TPQ) Darul Fallah 2 in improving the quality of children's ability to read the Qur'an is very significant. TPQ Darul Fallah 2 has several key elements that support the success of the learning process, including careful planning, the presence of teachers who live in one village, the preparation of a flexible curriculum, and the use of a structured tilawati learning method. In addition, adequate facilities and infrastructure and periodic learning evaluations also play an important role in achieving optimal results. Keywords: TPQ Darul Fallah 2; Qur'an Reading Ability; Children